BIOLOGICAL ACTIVITY EVALUATION OF OLEIC ACID-NICOTINE EMULSIONS OIL/WATER AGAINST Drosophila melanogaster - ARAQUE M, Pedronel; PELÁEZ J., Carlos A. (Vitae, 2010)
This paper studies the effect of the O/W emulsion of oleic acid-nicotine stabilized with Tween 80® on its acute and chronic insecticidal activity in Drosophila melanogaster. The oleic acid-nicotine emulsions acute bioactivity show a median lethal time (LT50 = 13 ± 3 minutes) significantly higher compared with that obtained with nicotine in aqueous solution (LT50 = 7 ± 1 minutes). Oleic acid-nicotine emulsion low bioactivity present high correlation with the percentage of nicotine encapsulated in emulsion droplets. The chronic bioactivity is assessed in the life cycle of D. melanogaster where diminution in oviposition is taken as evidence of repellency.